Changing Connectivities of Chinese Cities in the World City Network,2010–2016 - Derudder, Ben; Cao, Zhan; Liu, Xingjian; Shen, Wei; Dai, Liang; Zhang, Weiyang; Caset, Freke; Witlox, Frank; Taylor, Peter J. (Chinese geographical science, 2018)
Against the backdrop of the sizable economic growth of China in recent years, this paper uses the most recent data gathering of the Globalization and World Cities（Ga WC） research network to update and supplement earlier research on the shifting global connectivity of Chinese cities. The update consists of an evaluation of the connectivity of Chinese cities in 2016, the supplement of an analysis of the changing position of Chinese cities in the world city network between 2010 and 2016. To this end, we build on a specification of the world city network as an ‘interlocking network＇ in which producer services firms play the crucial role in city network formation. Information about the presence of leading producer services firms in cities in 2010 and 2016 is used as the input to a bipartite network projection algorithm in order to measure cities＇ network connectivity. The first set of results discusses the geographies of urban connectivity in the world city network in 2016. The second set of results discusses standardized measures of change to reveal the major dimensions of the transformations between 2010 and 2016. We find that, with the exception of Hong Kong, Macau and Kaohsiung of Taiwan, all Chinese cities record connectivity gains. This wholesale rise in connectivity is nonetheless geographically uneven, with above all Beijing, Chengdu/Chongqing and Changsha/Wuhan becoming more connected. We conclude that the wholesale rise of Chinese cities in the world city network and their changing trajectories in the post-crisis era are embedded in shifting external and internal political economies.